Academic Dishonesty: Assessing the Threat of Cheating Companies to Online Education. Issue 4 (1st October 2016) - Malesky, L. Alvin; Baley, John; Crow, Robert
ABSTRACT: Academic dishonesty has evolved to keep pace with changes in higher education. Websites now advertise the service of taking online courses for students. This study examined one such online company. Representatives from the company were professional and delivered the advertised services. Two experienced faculty members who co-taught the course used in this study were unable to identify the cheating company. The cheating company earned an "A" for the student. This article discusses the process by which the company was initially identified as well as provides an account of the interactions with the company that resulted in the student earning an "A."